Challenging the orthodoxy : Reflections on frank stilwell's contribution to political economy - Chester, Lynne; Schroeder, Susan K. (Springer Berlin Heidelberg, 2014)
Political economy focuses on issues that are fundamental to individual and collective well-being and rests on the proposition that economic phenomena do not occur in isolation from social and political processes. One leading Australian political economist is Frank Stilwell. Highlights of his work include concerns with the creation and use of wealth, inequalities between rich and poor, the spatial implications of economic growth, and the tensions between economic growth and the environment. Stilwell has been especially prominent in developing alternative economic policies, with seminal contributions to understanding the radical shift in Australian economic and social policies since the early 1980s. He has also been a leader in the teaching of political economy to many cohorts of first-year university students. This collection, spanning these themes, honours Stilwell's contribution to Australian political economy after more than 40 years teaching at the University of Sydney. The book provides not only an opportunity to appreciate his contribution but also a greater understanding of these themes which remain of crucial contemporary relevance.